Behavioral and Demographic Responses of Mule Deer to Energy Development on Winter Range. Issue 1 (15th January 2021) - Northrup, Joseph M.; Anderson, Charles R.; Gerber, Brian D.; Wittemyer, George
ABSTRACT: Anthropogenic habitat modification is a major driver of global biodiversity loss. In North America, one of the primary sources of habitat modification over the last 2 decades has been exploration for and production of oil and natural gas (hydrocarbon development), which has led to demographic and behavioral impacts to numerous wildlife species. Developing effective measures to mitigate these impacts has become a critical task for wildlife managers and conservation practitioners. However, this task has been hindered by the difficulties involved in identifying and isolating factors driving population responses. Current research on responses of wildlife to development predominantly quantifies behavior, but it is not always clear how these responses scale to demography and population dynamics. Concomitant assessments of behavior and population‐level processes are needed to gain the mechanistic understanding required to develop effective mitigation approaches. We simultaneously assessed the demographic and behavioral responses of a mule deer population to natural gas development on winter range in the Piceance Basin of Colorado, USA, from 2008 to 2015. Notably, this was the period when development declined from high levels of active drilling to only production phase activity (i.e., no drilling). We focused our data collection on 2 contiguous mule deer winter range study areas that experienced starkly different levels of hydrocarbon development within the Piceance Basin. We assessed mule deer behavioral responses to a range of development features with varying levels of associated human activity by examining habitat selection patterns of nearly 400 individual adult female mule deer. Concurrently, we assessed the demographic and physiological effects of natural gas development by comparing annual adult female and overwinter fawn (6‐month‐old animals) survival, December fawn mass, adult female late and early winter body fat, age, pregnancy rates, fetal counts, and lactation rates in December between the 2 study areas. Strong differences in habitat selection between the 2 study areas were apparent. Deer in the less‐developed study area avoided development during the day and night, and selected habitat presumed to be used for foraging. Deer in the heavily developed study area selected habitat presumed to be used for thermal and security cover to a greater degree. Deer faced with higher densities of development avoided areas with more well pads during the day and responded neutrally or selected for these areas at night. Deer in both study areas showed a strong reduction in use of areas around well pads that were being drilled, which is the phase of energy development associated with the greatest amount of human presence, vehicle traffic, noise, and artificial light. Despite divergent habitat selection patterns, we found no effects of development on individual condition or reproduction and found no differences in any of the physiological or vital rate parameters measured at the population level. However, deer density and annual increases in density were higher in the low‐development area. Thus, the recorded behavioral alterations did not appear to be associated with demographic or physiological costs measured at the individual level, possibly because populations are below winter range carrying capacity. Differences in population density between the 2 areas may be a result of a population decline prior to our study (when development was initiated) or area‐specific differences in habitat quality, juvenile dispersal, or neonatal or juvenile survival; however, we lack the required data to contrast evidence for these mechanisms. Given our results, it appears that deer can adjust to relatively high densities of well pads in the production phase (the period with markedly lower human activity on the landscape), provided there is sufficient vegetative and topographic cover afforded to them and populations are below carrying capacity. The strong reaction to wells in the drilling phase of development suggests mitigation efforts should focus on this activity and stage of development. Many of the wells in this area were directionally drilled from multiple‐well pads, leading to a reduced footprint of disturbance, but were still related to strong behavioral responses. Our results also indicate the likely value of mitigation efforts focusing on reducing human activity (i.e., vehicle traffic, light, and noise). In combination, these findings indicate that attention should be paid to the spatial configuration of the final development footprint to ensure adequate cover. In our study system, minimizing the road network through landscape‐level development planning would be valuable (i.e., exploring a maximum road density criteria). Lastly, our study highlights the importance of concomitant assessments of behavior and demography to provide a comprehensive understanding of how wildlife respond to habitat modification. © 2021 The Wildlife Society. SUMMARY OF CONCLUSIONS AND MANAGEMENT IMPLICATIONS: Adult female mule deer showed substantial behavioral plasticity in the face of natural gas development, with no apparent demographic consequences. Topographically diverse winter range with adequate vegetation providing sufficient food and cover allow deer to alter behavior in an adaptive manner, and similar features should be considered in future development planning. Réponses démographiques et comportementales du cerf mulet aux développements énergétiques sur leur aire d'hivernage: RÈSUMÈN Les modifications anthropogéniques de l'habitat sont une source majeure de la perte de biodiversité. En Amérique du Nord, l'une des sources importantes de modification de l'habitat durant les deux dernières décennies est reliée à l'exploration et à la production d'huile et de gaz naturel (développements reliés aux hydrocarbures). Ces développements ont causé des impacts démographiques et comportementaux pour de nombreuses espèces fauniques. Développer des mesures efficaces afin de réduire ces impacts est devenu une tâche importante des gestionnaires de la faune et des conservationnistes. Cependant, cette tâche a été compliquée par les difficultés associées à l'identification des facteurs influençant les réponses de la population aux développements. Les recherches portant sur les réponses de la faune aux développements quantifient principalement le comportement, mais il n'est pas toujours facile de comprendre comment ces réponses sont reliées à la démographie et à la dynamique des populations. Une évaluation concomitante du comportement et des processus de la population sont requis afin d'obtenir une compréhension mécanistique permettant de développer des mesures de mitigation appropriées. Nous avons évalué simultanément les réponses démographiques et comportementales d'une population de cerf mulet sur leur aire d'hivernage, associées au développement relié au gaz naturel dans le bassin Piceance du Colorado, USA, entre 2008 et 2015. Ceci correspondait à la période où le niveau de développement a fluctué de façon importante, entre une phase de forage active et une phase de production (sans forage). Nous avons concentré notre collection de données sur deux aires d'hivernage adjacentes qui ont subi des niveaux différents de développement reliés aux hydrocarbures à l'intérieur du bassin Piceance. Nous avons évalué la réponse comportementale des cerfs mulets aux attributs reliés au développement avec des niveaux variés d'activités humaines en examinant la sélection d'habitat de près de 400 femelles cerfs mulets. Nous avons aussi évalué l'effet des développements reliés au gaz naturel sur la démographie et la physiologie en comparant la survie annuelle des femelles adultes et la survie hivernale des faons (âgés de 6 mois), les réserves de gras des femelles au début et à la fin de l'hiver, l'âge, le taux de gestation et le taux de lactation en décembre entre les deux aires d'études. Des différences majeures au niveau de la sélection d'habitat ont été observées entre les deux aires d'études. Les cerfs habitant l'aire d'étude moins développée évitaient les zones développées durant le jour et la nuit et sélectionnaient des habitats afin de s'alimenter. Les cerfs habitant l'aire d'étude plus développée sélectionnaient plus fortement des habitats à des fins de sécurité et de couvert thermal. Les cerfs faisant face à une plus grande densité de développement évitaient les endroits avec une plus grande densité de puits durant le jour alors qu'ils n'évitaient pas ou sélectionnaient ces endroits durant la nuit. Les cerfs habitant les deux aires d'études montraient une réduction importante de l'utilisation des puits durant leur forage, ce qui correspondait à la phase de développement avec la plus grande présence humaine, circulation automobile, bruit, et lumière artificielle. Malgré des patrons de sélection d'habitat divergents, nous n'avons pas détecté un effet des développements sur la condition ou la reproduction et nous n'avons pas trouvé de différence chez les taux vitaux ou physiologiques mesurés au niveau de la population. Cependant, la densité de cerfs et le taux de changement annuel dans la densité étaient supérieurs dans l'aire d'étude moins développée. Les changements comportementaux mesurés ne semblaient donc pas être associés avec des coûts démographiques ou physiologiques au niveau individuel, possiblement parce que les populations étaient sous la capacité biotique de l'aire d'hivernage. Les différences entre les densités de population entre les deux aires d'études sont peut‐être dû à un déclin de la population précédant notre étude (lorsque le développement démarrait) ou à des différences au niveau de la qualité de l'habitat, du dispersement ou de la survie des nouveau‐nés ou des juvéniles. Cependant, nous manquons les données requises pour contraster ces mécanismes. Selon nos résultats, il apparait que les cerfs mulets peuvent s'adapter à une densité élevée de puits durant la phase de production (la période avec moins d'activités humaines) si la quantité de protection offerte par la végétation et la topographie est suffisante et si la population est sous la capacité biotique. La forte réponse aux puits durant la période de forage indique que les mesures de mitigation devraient prioriser ces activités et ce stade de développement. Plusieurs des puits de la région étaient percés directionnellement à partir d'un même endroit, entraînant une réduction de l'emprise, mais ils entrainaient néanmoins une réponse comportementale des cerfs. Nos résultats démontrent aussi l'importance potentielle de mesures de mitigation tentant de réduire le niveau d'activité humaine (i.e. la circulation automobile, la lumière et le bruit). Nos résultats soulignent l'importance de porter attention à la configuration spatiale du développement afin d'assurer un niveau de couvert suffisant. Dans notre système, minimiser le réseau des routes en utilisant une planification au niveau du paysage pourrait être utile (i.e. explorer un critère maximum pour la densité de route). Dernièrement, notre étude a démontré l'importance d'évaluer en même temps le comportement et la démographie afin de procurer une compréhension globale de la réponse de la faune aux modifications de l'habitat.